EFFECT OF TURNOVER OF CASH, RECEIVABLES TURNOVER AND INVENTORY TURNOVER OF LIQUIDITY IN GENERAL AREA PEARL HARAPPAN - Sefnat Aristarkus Tang; Yustina Maro; Junius Menase Sau Sabu (Universitas Mercu Buana, 2021)
Liquidity is the company's ability to pay off its short-term obligations. The higher the level of liquidity, the more capable the company is to pay off its obligations, conversely, the lower the liquidity, the lower the company's ability to pay off its obligations. This study aims to determine the effect of cash turnover, accounts receivable turnover, and inventory turnover on liquidity as represented by the current ratio at the Harappan Regional Public Company, Alor Regency, either partially or simultaneously. Data collection was carried out using documentation techniques by taking samples in the form of financial reports for 2015-2019. Data analysis used descriptive statistics, multiple linear regression, t-test, and F test. The results showed that partially cash turnover had a positive significant effect on company liquidity. Accounts receivable turnover has a positive significant effect on company liquidity, and inventory turnover has a positive significant effect on the Company's liquidity. Simultaneously, cash turnover, accounts receivable turnover and inventory turnover have a positive significant effect on company liquidity.